Google Drive as Instructional Media to Facilitate Students’ Assignment Submission: Opportunities and Challenges - Andi Bulkis Magfirah Mannong (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
In the 21st century of learning, the usage of technology has become an important role in education. Google drive, as media in collecting assignment, is able to improve the effectiveness and efficiency of student assignment management. This study aims to explore the use of Google Drive in the submission of student assignments in English language learning. This study used a descriptive qualitative method by using questionnaire as a technique in data collection. The subjects of this study were 50 English department students. The results showed that besides assisting students in assignment collection management and increasing technological literacy, the use of technology also helps improve student collaboration and independent learning. However, it also found that the challenges faced by the students are not only related to accessibility, but also the lack of understanding Google Drive features, thus it makes some students are errors in uploading assignments. This study concluded that Google Drive can help to improve the quality of English language learning with some adjustments related to technical constraints and understanding of Google Drive features need to be overcome to make the assignment collection process goes smoothly and effectively.